Effect of Surgical Trainee Presence on Vaginal Hysterectomy Outcomes. Issue 1 (January 2019) - Rajakumar, Chandrew; Mallick, Ranjeeta; Posner, Glenn; Schramm, David; Singh, Sukhbir S.; Lortie, Karine; Pascali, Dante; Chen, Innie
Abstract : (Abstracted from J Minim Invasive Gynecol 2018;25:1088–1093) Definitive relief from several disease states that burden women can be provided by hysterectomy. This procedure can be performed via vaginal, laparoscopic, robotic, transabdominal, or combined approaches.